BDNF Val66Met genotype interacts with childhood adversity and influences the formation of hippocampal subfields. Issue 12 (10th July 2014) - Frodl, Thomas; Skokauskas, Norbert; Frey, Eva‐Maria; Morris, Derek; Gill, Michael; Carballedo, Angela
Abstract Childhood stress and genetic factors like the Val66MET polymorphism of the brain derived neurotrophic factor (BDNF) gene are associated with a higher risk for developing major depressive disorder (MDD) and might also influence hippocampal changes. The aim of this study was to determine which hippocampal dentate gyrus and cornu ammonis subfields are altered in MDD compared to healthy controls and which subfields are affected by the BDNF Val66Met polymorphism and child adversity. Adult patients with MDD and healthy matched controls underwent high‐resolution magnetic resonance imaging. Automatic segmentation using the programme FreeSurfer was used to segment the hippocampal subfields dentate gyrus (DG/CA4), CA1 and CA2/3. The history of possible childhood adversity was assessed using the Childhood Trauma Questionnaire and the Val66Met BDNF SNP (rs6265) genotypes were obtained. Patients with MDD had significantly smaller CA4/DG and CA2/3 volumes compared to healthy controls. Furthermore, there was a significant interactive effect of BDNF allele and childhood adversity on CA2/3 and CA4/DG volumes. Met allele carriers without childhood adversity had larger and with childhood adversity smaller CA4/DG and CA2/3 volumes than Val‐allele homozygotes. Our results highlight stress by gene interactions as relevant for hippocampal volume reductions, in particular for the subfield CA2/3 and dentate gyrus. Hum Brain Mapp 35:5776–5783, 2014. © 2014 Wiley Periodicals, Inc.